Education Marketing Management Strategy in Increasing the Interest of Prospective Students from a Competitive Advantage Perspective - Romli, Ombi; Asyiah, Euis; Supianto,; Enung Nugraha,; Naf'an Tarihoran, (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to analyze and formulate an education marketing management strategy that is able to increase the interest of prospective students by integrating the principle of competitive advantage in Islamic boarding school educational institutions. This Islamic Boarding School implements a donor-based free education model. Using a qualitative approach with case study methodology, data were collected through in-depth interviews with 15 key informants, participant observation, and documentation studies during July 2025. The research findings indicate that the implementation of the 7P marketing mix adapted for the donor-based Islamic Boarding School context has created a competitive advantage reflected in student growth exceeding targets (50% in 2024), funding stability with an average monthly donation of IDR 350,000,000, and 67% brand awareness in the Greater Jakarta area. Educational program quality emerged as the dominant factor (37%) in attracting prospective students, supported by a professional donor management system with a 92% satisfaction rate. The educational marketing model developed by the Islamic Boarding School offers a new paradigm in democratizing quality education for orphans and underprivileged communities, while simultaneously providing a framework for developing donor-based Islamic Boarding Schools.